Psychosocial stress, food preferences, and screen time with nutritional status of women of reproductive age in Sukamulya Village, Tangerang Regency - Badriyah, Siti; Melani, Vitria; Sitoayu, Laras; Dewanti, Lintang Purwara; Ronitawati, Putri (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2023)
Background: The increase in age and the pandemic conditions experienced cause Women of Reproductive Age (WRA) to encounter many environmental issues that disturb their psyche, resulting in psychosocial stress. A strategy for dealing with stress is called coping with stress. A higher screen time and high sugar, salt, or fat to deal with stress might change nutritional status.Objective: This study aims to determine the relationship between psychosocial stress, food preferences, and screen time with the nutritional status of WRA in Sukamulya Village, Tangerang Regency.Materials and Methods: This research design is cross-sectional and was conducted in March 2022 in Sukamulya Village, Tangerang Regency. The research sample amounted to 55 participants with a purposive sampling technique. The questionnaires used were Psychosocial Stress Assessment Instrument, Food Frequency Questionnaires, and recall screen time. Data analysis using the Chi-Square test.Results: The majority of participants experienced psychosocial stress (61.8%), food preferences low in sugar, salt, and fat (63.6%), and most of them were in the high screen time category (52.7%). The results showed that there was no relationship between psychosocial stress and food preferences with nutritional status (p > 0.05), but there was a relationship between screen time and nutritional status (p = 0.011).Conclusion: In this study, food preferences and psychosocial stress were not factors that affected the nutritional status.